1998
DOI: 10.1152/ajpcell.1998.274.4.c1017
|View full text |Cite
|
Sign up to set email alerts
|

Identification of clathrin and clathrin adaptors on tubulovesicles of gastric acid secretory (oxyntic) cells

Abstract: γ-Adaptin and clathrin heavy chain were identified on tubulovesicles of gastric oxyntic cells with the anti-γ-adaptin monoclonal antibody (MAb) 100/3 and an anti-clathrin heavy chain MAb (MAb 23), respectively. In Western blots, crude gastric microsomes from rabbit and rat and density gradient-purified, H-K-ATPase-rich microsomes from these same species were immunoreactive for γ-adaptin and clathrin. In immunofluorescent labeling of isolated rabbit gastric glands, anti-γ-adaptin and anti-clathrin heavy chain i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
29
1

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 56 publications
1
29
1
Order By: Relevance
“…Once the proton pump is localized at the apical membrane, acid secretion into the lumen of the stomach takes place. Upon return to the resting state, proton pumps are sequestered back into tubulovesicles, a process thought to involve clathrin-coated vesicle formation similar to endocytosis (13,21). Previous gene expression microarray studies of purified parietal cells showed abundant expression of Hip1r but little or no Hip1 (14), suggesting that Hip1r may serve a unique function in parietal cells (5,8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the proton pump is localized at the apical membrane, acid secretion into the lumen of the stomach takes place. Upon return to the resting state, proton pumps are sequestered back into tubulovesicles, a process thought to involve clathrin-coated vesicle formation similar to endocytosis (13,21). Previous gene expression microarray studies of purified parietal cells showed abundant expression of Hip1r but little or no Hip1 (14), suggesting that Hip1r may serve a unique function in parietal cells (5,8).…”
Section: Discussionmentioning
confidence: 99%
“…Upon stimulation of the parietal cell, tubulovesicles fuse with the apical plasma membrane to form an expanded surface membrane termed the canaliculus, which is capable of acid secretion into the lumen of the stomach. To return the parietal cell to the basal state, tubulovesicles containing the proton pump are reformed through a process thought to involve clathrin-coated vesicle formation similar to endocytosis (13). Thus, parietal cells rely on vesicular fusion and reformation to regulate acid secretion.…”
Section: Introductionmentioning
confidence: 99%
“…Another potentially relevant finding is that there is a fairly well conserved clathrin adaptor motif in coronin se . Since clathrin and clathrin adaptors have recently been localized to tubulovesicular membranes in parietal cells (36), it is possible that there is a regulated interaction between coronin se and clathrin or a related protein that serves to direct, for example, the endocytic retrieval of the H ϩ ,K ϩ -ATPase from the apical membrane to subapical tubulovesicular membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Upon stimulation, tubulovesicles containing H ϩ ,K ϩ -ATPase are incorporated into the apical membrane, the latter acquiring K ϩ and Cl Ϫ permeability, and thus H ϩ ,K ϩ -ATPase can exchange K ϩ for protons, creating HCl together with water secretion (1). Recent studies on mechanisms of membrane fusion in parietal cells have made rapid progress, and several proteins involved in the recruitment/recycling process have been identified (2)(3)(4). In contrast, little is known of how the apical membrane acquires K ϩ and Cl Ϫ ion permeability, which is thought to be the direct trigger for activation of the H ϩ ,K ϩ -ATPase.…”
mentioning
confidence: 99%